Strategi Pengelolaan Risiko Dalam Menangani Kenakalan Remaja Di Sekolah SMA Setia Dharma Pekanbaru - Putri, Meliza; Hidayat, Wahyu (Edification Journal : Pendidikan Agama Islam, 2023)
Adolescence is a time when humans search for their own identity. Many of them cannot find their identity as a result of some of their influences. Until now, various forms of juvenile delinquency are often found. However, it is difficult to eliminate the forms of risk of deviant behavior carried out by teenagers today because this is influenced by friends, family, parents or schools. This study aims to determine the extent to which schools can manage the risk of juvenile delinquency in their students. With research conducted qualitatively, it gives the result that schools manage the risk of delinquency by conducting seminars, guidance from counseling teachers and so on. If, it is found that students violate it, the school will give a warning before taking further action, namely expelling them from school.